2019
DOI: 10.3390/pharmacy7040152
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Immunizing Pharmacy Technicians in a Federal Healthcare Facility

Abstract: Background: Pharmacy technicians are legally allowed to administer immunizations in specific U.S. states, provided they meet certain criteria, including the completion of an accredited immunization training course. Immunizing pharmacy technicians were incorporated into an Indian Health Services federal facility, Whiteriver Service Unit (WRSU), in 2018. The objective of this research was to gather information about implementing immunizing pharmacy technicians in a federal facility serving a large rural and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…In addition, pharmacists who worked with trained technician immunizers in a federal facility reported it improved workflow greatly, allowing pharmacists to provide more clinical services. 53 Therefore, greater empowerment of pharmacy technicians as immunizers seems to expand the opportunity for advanced pharmacist services.…”
Section: Image Of Pharmacy Professionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pharmacists who worked with trained technician immunizers in a federal facility reported it improved workflow greatly, allowing pharmacists to provide more clinical services. 53 Therefore, greater empowerment of pharmacy technicians as immunizers seems to expand the opportunity for advanced pharmacist services.…”
Section: Image Of Pharmacy Professionmentioning
confidence: 99%
“…45 Similarly, pharmacists supervising technician immunization administrators in a federal facility reported their support for the effort and encouraged other technicians to participate in training. 53 Pharmacist comfort is likely also aided by reports of safety. McKeirnan et al 13 and McKeirnan and Sarchet 53 reported 953 immunizations with no reported adverse events in community pharmacy settings and 4852 vaccinations given in a federal health care facility without issue.…”
Section: Pharmacist and Technician Comfort With Technician Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one study was published within the last 5 years. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] The majority of included studies were conducted in community pharmacies (85.7 %, n ¼ 12) [22][23][24][25][26][27][28][29][30][31]33,34 with one inpatient hospital study 21 and one outpatient hospital study that included vaccination clinics. 32 With the exception of one Canadian paper, 29 all of the included studies took place in the United States (92.8%, n ¼ 13) spanning 8 states.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Similarly, studies focused on medication history collection have found that pharmacy technicians are accurate and time efficient and, in some cases, may also decrease costs [4,5]. In terms of immunization administration, McKeirnan and Sarchet have affirmed that appropriately trained pharmacy technicians improve access to vaccination care, thereby having the potential to increase the number of immunizations given and reduce the number of deaths from vaccine-preventable diseases [6].…”
mentioning
confidence: 99%